Elders-in-Residence at Vancouver Island University: Transformational Learning ... - Martin, Melody; Meijer Drees, Laurie (Vancouver Island University, 2011)
Postsecondary educational institutions across Canada are increasingly committed to addressing the historical disadvantage of aboriginal learners within their programs. Overall, involvement of Elders is perceived as a positive strategy for improving aboriginal student success. Vancouver Island University in British Columbia has, since 1994, pioneered the employment of aboriginal Elders-in-Residence. The findings of this study, based on the question "What is the value and impact of the role of Elders-in-Residence at Vancouver Island University?" emphasize the positive contribution Elders from local First Nations communities make to daily life on campus, whether in the classroom or at large. Although the study does reveal that concerns exist about the respect and support for, and the nature of, the role of the Elders as teachers, all respondents nonetheless believed in the value of the positions. The study concludes with four important recommendations for improving, clarifying and acknowledging the important ...